Biological growth and development in skating performance, muscle structure and anerobic power output capacity in male and female Japanese speed skaters - Kumagawa, D.; Tsunoda, N. (Japanese Journal of Physical Fitness and Sports Medicine, 2008)
The objective of this study was to examine biological growth and development in skating performance by focusing on thigh muscle thickness and anaerobic power output capacity in Japanese speed skaters. One hundred thirty-three male and 96 female skaters aged from 10 to 22 years old were tested in this study. The anterior (MTA) and posterior (MTP) thicknesses of the thigh muscles were measured by the B-mode ultrasonic method. Maximal anaerobic power output capacity (MAP) was determined using a bicycle ergometer. The mean 500m skating velocity (SV), calculated from recently attained individual best times, was used as a measure of skating performance. These parameters, along with height, were plotted on a logarithmic graph to obtain the allometric equation y=bx^a, where "a" is a growth index. There were two sharp bends in the graph showing the relationships between MTA, MTP, MAP, SV and body height in both males and females. The growth indexes "a" between the first and second changing points in all the above relationships were observed to be larger than the other phases. Ranges of body height between the first and second changing point in muscle thicknesses (MTA, MTP) ranged from 152.2-154.8cm to 168.1-168.3cm in males, and from 142.8-144.9cm to 154.4-157.6cm in females. The ranges of MAP were from 139.8cm to 166.8cm in males, and from 138.8cm to 157.8cm in females. However, the height ranges of SV were from 147.4cm to 167.8 cm in males, and from 142.2 cm to 153.2cm in females. From these results, it was suggested that accelerated development of skating performance and anaerobic power output capacity begins earlier than muscle structural development in speed skaters.